Different apoptotic effects of [Pt(O, O′‐acac)(γ‐acac)(DMS)] and cisplatin on normal and cancerous human epithelial breast cells in primary culture. (5th September 2014) - Vetrugno, Carla; Muscella, Antonella; Fanizzi, Francesco Paolo; Cossa, Luca Giulio; Migoni, Danilo; De Pascali, Sandra Angelica; Marsigliante, Santo
<x xml:space="preserve">Abstract</x> Background and Purpose The aim of this study was to determine whether [platinum (Pt)(O, O′‐acetylacetonate (acac))(γ‐acac)(dimethylsulphide (DMS))] is differentially cytotoxic in normal and cancer cells, and to measure comparative levels of cytotoxicity compared with cisplatin in the same cells. Experimental Approach We performed experiments on cancerous and normal epithelial breast cells in primary culture obtained from the same patients. The apoptotic effects [Pt(O, O′‐acac)(γ‐acac)(DMS)] and cisplatin in cancerous and normal breast cells were compared. Key Results Cancer cells were more sensitive to [Pt(O, O′‐acac)(γ‐acac)(DMS)] (IC50 = 5.22 ± 1.2 μmol·L−1) than normal cells (IC50 = 116.9 ± 8.8 μmol·L−1). However, the difference was less strong when cisplatin was used (IC50 = 96.0 ± 6.9 and 61.9 ± 6.1 μmol·L−1 for cancer and normal cells respectively). Both compounds caused reactive oxygen species (ROS) production with different mechanisms: [Pt(O, O′‐acac)(γ‐acac)(DMS)] quickly activated NAD(P)H oxidase while cisplatin caused a slower formation of mitochondrial ROS. Cisplatin and [Pt(O, O′‐acac)(γ‐acac)(DMS)] caused activation of caspases, proteolysis of PARP and modulation of Bcl‐2, Bax and Bid. [Pt(O, O′‐acac)(γ‐acac)(DMS)] also caused leakage of cytochrome c from the mitochondria. Overall, these processes proceeded more quickly in cells treated with [Pt(O, O′‐acac)(γ‐acac)(DMS)] compared with cisplatin. [Pt(O, O′‐acac)(γ‐acac)(DMS)] effects were faster and quantitatively greater in cancer than in normal cells. [Pt(O, O′‐acac)(γ‐acac)(DMS)] caused a fast decrease of mitochondrial membrane potential, especially in cancer cells. Conclusions and Implications [Pt(O, O′‐acac)(γ‐acac)(DMS)] was specific to breast cancer cells in primary culture, and this observation makes this compound potentially more interesting than cisplatin.